Empowerment of Persons with Disabilities Affected by Covid-19 Through Assistance in Repairing Disability Motorcycles - Supartono, Basuki; Kusumaningsih, Prita; Zahra, Dewi Fatimah (Indonesian Red Crescent Humanitarian Journal, 2022)
People with disabilities are numerous, reaching 15% of the Indonesian population. Some are independent and make a living by trading around using special motorcycles (disabled motorcycles) as done by members of the Independent Disability Shelter House (Rumsidisma), Rawa Lumbu, Bekasi, West Java. They can not make a living because the motorbike is damaged while they do not have repair funds. This hampered income, and this problem further disrupted their lives during the Covid-19 pandemic. Therefore, it is necessary to carry out community service activities (PKM) to provide funds for repairing disability motorcycles. This activity aims to help people with disabilities in Rumsidisma to be able to earn a living and be independent as before. The method of implementing PKM includes the stages of preparation, implementation, and evaluation. Implementation activities include providing funds and repairing disability motorcycles. Evaluation is carried out through interviews and filling out evaluation forms. All activity processes are carried out by implementing health protocols. PKM activities can repair three disabled motorcycles. Member of Rumsdisma. Can return to making a living and be as independent as before. RecipientsRecembly of assistance were satisfied and agreed that this activity was continued. There were no reports that PKM implementers and beneficiaries were infected with Covid-19. The conclusion is that repairing of the disability motorcycles of Rumsidisma members during the pandemic has been successfully carried out safely and can empower members as before.